(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify the prevalence and factors associated with Metabolic Syndrome in patients treated at a multiprofessional outpatient clinic for perioperative medicine and nursing. Methods: This is a descriptive, documentary cross-sectional study, with a quantitative approach, performed on the medical records of patients undergoing pre-anesthetic evaluation in a perioperative medicine and nursing clinic. Results: The prevalence of Metabolic Syndrome (MS) was 54.4%. The studied population was characterized by the predominance of female individuals (67.6%), the average age was 62.36 years with and standard deviation of 13.69. There was a significant association with age, BMI, OSAHS, SAH, DM and ASA Conclusion: The parameters related to the components of the metabolic syndrome were increased for waist circumference, SBP, DBP, GJ, and TG, and reduced for HDL among those diagnosed with MS. In addition, BMI values ​​indicative of overweight and obesity and the presence of SAH and DM were observed.